2014
DOI: 10.1039/c4nr01202j
|View full text |Cite
|
Sign up to set email alerts
|

In vivo delivery of bovine viral diahorrea virus, E2 protein using hollow mesoporous silica nanoparticles

Abstract: Our work focuses on the application of mesoporous silica nanoparticles as a combined delivery vehicle and adjuvant for vaccine applications. Here we present results using the viral protein, E2, from bovine viral diarrhoea virus (BVDV). BVDV infection occurs in the target species of cattle and sheep herds worldwide and is therefore of economic importance. E2 is a major immunogenic determinant of BVDV and is an ideal candidate for the development of a subunit based nanovaccine using mesoporous silica nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 46 publications
0
60
0
Order By: Relevance
“…All the animals remained healthy throughout the duration of the trial and none of the nanovaccine formulations caused localised skin redness or reaction at the site of the injection, indicating that the SV were very well tolerated in mice. The treatment groups injected with oE2/SV-140 (50 mg/250 mg) induced excellent antibody response at 10 5 titre, which was higher than the positive control group oE2 (50 mg) plus Quil A (10 mg) (10 4 titre) as well as the responses generated by the mice treated with oE2/ HMSA (10 3 titre) [23]. In addition to elicitation of the humoral response, the oE2/SV-140 induced a stronger and higher memory response (1954e2628 SFU/million cells) compared to the group treated with Quil A (512e1369 SFU/million cells).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…All the animals remained healthy throughout the duration of the trial and none of the nanovaccine formulations caused localised skin redness or reaction at the site of the injection, indicating that the SV were very well tolerated in mice. The treatment groups injected with oE2/SV-140 (50 mg/250 mg) induced excellent antibody response at 10 5 titre, which was higher than the positive control group oE2 (50 mg) plus Quil A (10 mg) (10 4 titre) as well as the responses generated by the mice treated with oE2/ HMSA (10 3 titre) [23]. In addition to elicitation of the humoral response, the oE2/SV-140 induced a stronger and higher memory response (1954e2628 SFU/million cells) compared to the group treated with Quil A (512e1369 SFU/million cells).…”
Section: Discussionmentioning
confidence: 93%
“…A recent finding, showed that intramuscular immunisation with a dose of 100 mg PCV2 per 0.7 mg HMSNs particles generated PCV2-specific antibody serum response as well as T-cell responses [35]. Previously, we have reported the induction of humoral and cellmediated immune responses by amino functionalised MSNs as well as HMSAs [23,25], however due to the low loading of proteins obtained on the nanoparticles, a direct comparison between the positive control group comprising of conventional adjuvant and the nanovaccine treatment could not be performed. In the current research study, the improvement in the particle design enabled us to directly compare the immune responses generated by the conventional adjuvant used in the positive control group (oE2 plus Quil A) and the nanovaccine treatment group.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations